VIRTUAL INTERACTIVE TUTORIAL SYSTEM FOR CALCULUS - MOHAMAD RODZI, MOHO ERWAN SYAFIQ (Universiti Teknologi PETRONAS, 2011)
Every higher education nowadays uses e-learning as the best way to interact between lecturers and students. Web-based learning is widely used nowadays to support a process of teaching and learning as it is more interactive than traditional ways of teaching. This paper focuses more on developing a Web-based learning environment for Calculus. The main objective for this project is to develop a Virtual Interactive Tutorial System for Calculus using Web-based learning where students can utilize internet technology to gain Output learning. This project involved three important tools which is PHP programming language, MySQL database management system and XAMPP server. Firstly we write a source code for our system using PHP language, then we store our database using MySQL and finally we test our system on local server using XAMPP.